Pencantuman Syarat Berpenampilan Menarik Dalam Lowongan Pekerjaan Ditinjau dari Prinsip Non-Diskriminasi Berdasarkan Undang-Undang Nomor 13 Tahun 2003 dan Peraturan Menteri Ketenagakerjaan Nomor 14 Tahun 2025 - Amaliano Galang Ramadhana; Ahmad Sholikhin Ruslie (Media Hukum Indonesia (MHI), 2026)
The practice of including "attractive appearance" as a requirement in job vacancies is still widely found in the Indonesian labor market. Although considered normal by some employers, this requirement actually harbors potential for indirect discrimination due to its highly subjective nature. This study aims to analyze the legality of attractive appearance requirements in the recruitment process viewed from the non-discrimination principles regulated in Law Number 13 of 2003 concerning Labor and the Regulation of the Minister of Manpower Number 14 of 2025. The research method used is normative legal research with statutory, conceptual, and comparative law approaches. The results of the analysis show that the requirement of attractive appearance is a form of vague norm that violates the principle of legal certainty and undermines the meritocracy system in the workplace. Through Minister of Manpower Regulation Number 14 of 2025, the government explicitly prohibits physical requirements that are not directly related to the main function of the job (Bona Fide Occupational Qualifications). This study concludes the need for a reconstruction of recruitment patterns in Indonesia through the standardization of job vacancy language based on professional behavior, the implementation of anonymous selection (blind recruitment), and the optimization of digital inspection of job advertisements